Digital Evangelism and the Mediatization of Nigerian Pentecostalism: New Media and the Transformation of Religious Communication in the Twenty-First Century - Odewale, Victor Taiwo (European Scientific Journal, ESJ, 2026)
The rapid proliferation of digital communication technologies has significantly transformed the structure and practice of religion worldwide. Nigerian Pentecostal churches have emerged as particularly innovative adopters of new media platforms for evangelism, religious instruction, and global networking. The Pentecostal churches have been particularly innovative in adopting digital media for evangelistic outreach and global religious engagement. This article examines how digital media—including social networking platforms, livestreaming technologies, and digital broadcasting systems—have reshaped religious authority, worship practices, and transnational expansion within Nigerian Pentecostalism. Drawing on mediatization theory, globalization theory, and religious economy theory, the study analyses the digital communication strategies of major Nigerian Pentecostal ministries. The article argues that digital evangelism has enabled Nigerian Pentecostal churches to transcend geographical boundaries and construct global religious communities while simultaneously generating new challenges such as commercialization, exploitation, doctrinal fragmentation, and the virtualization of worship which leads to fragmentation of African community life. The study contributes to the growing scholarship on digital religion and the globalization of African Christianity.